George VI and Elizabeth : the marriage that saved the monarchy - Smith, Sally Bedell, 1948- (Random House, 2023)
"When the Duke of Windsor abdicated the throne in 1936, his shy, uncertain, unprepared younger brother became King. Sally Bedell Smith was granted by Queen Elizabeth II special access to the letters and diaries of George VI and Elizabeth, to tell the story of how their love, devotion, and strong marriage led George VI to overcome insecurities and difficulty speaking and to become an exceptional leader. His wife Elizabeth, a pretty, confident, and outgoing woman, who became known later in life as "the Queen Mum," simultaneously strengthened and advised her temperamental husband, while raising the future Queen Elizabeth II (who at an early age was educated to lead, and fell in love at 15 with Prince Philip) and Princess Margaret. Sally Bedell Smith explores how this loving and devoted marriage helped the king and queen meet the challenges of leading the country through war, London during the blitz, their relationship with Winston Churchill, their visit with Franklin and Eleanor Roosevelt in Washington and Hyde Park, and more"--